2009
DOI: 10.1128/jb.00119-09
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Rugose Small-Colony Variants Have Adaptations That Likely Promote Persistence in the Cystic Fibrosis Lung

Abstract: Pseudomonas aeruginosa is recognized for its ability to colonize diverse habitats, ranging from soil to immunocompromised people. The formation of surface-associated communities called biofilms is one factor thought to enhance colonization and persistence in these diverse environments. Another factor is the ability of P. aeruginosa to diversify genetically, generating phenotypically distinct subpopulations. One manifestation of diversification is the appearance of colony morphology variants on solid medium. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
471
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(504 citation statements)
references
References 44 publications
(66 reference statements)
12
471
1
1
Order By: Relevance
“…Several of the mutations and phenotypes that we have observed among sinus isolates, evolved in parallel in the different patients, including those conferring loss of motility and quorum sensing signals (virulence), alginate overproduction, antibiotic resistance and increased biofilm formation (SCVs). (Cabral et al, 1987;Mahenthiralingam et al, 1994;Haussler et al, 1999;Smith et al, 2006;D'Argenio et al, 2007;Starkey et al, 2009;Hoffman et al, 2010). Most of them are generally thought to be beneficial also in the lung environment through the development of resistance to host defenses and antibiotics or to optimized utilization of available nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the mutations and phenotypes that we have observed among sinus isolates, evolved in parallel in the different patients, including those conferring loss of motility and quorum sensing signals (virulence), alginate overproduction, antibiotic resistance and increased biofilm formation (SCVs). (Cabral et al, 1987;Mahenthiralingam et al, 1994;Haussler et al, 1999;Smith et al, 2006;D'Argenio et al, 2007;Starkey et al, 2009;Hoffman et al, 2010). Most of them are generally thought to be beneficial also in the lung environment through the development of resistance to host defenses and antibiotics or to optimized utilization of available nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Sinuses are infection foci in CF airways SK Hansen et al studies documented the presence of SCVs in the sinus populations, but CF lung SCV isolates have some additional characteristics besides the small colony form (Haussler et al, 1999;Starkey et al, 2009). Sinus SCV isolates were therefore further analyzed for these specific phenotypes: clumping in liquid culture, decreased motility, enhanced biofilm formation and antibiotic resistance (Figure 3).…”
Section: Sinus Isolates With Increased Antibiotic Resistance From Patmentioning
confidence: 99%
“…A mutant screen in Yersinia pestis resulted in the identification of three c-di-GMP-modulating proteins playing a role in attachment and biofilm formation, including the DGC HmsT and the PDE HmsP, which inversely regulate biofilm formation by controlling the synthesis of the polysaccharide poly-␤-1,6-N-acetylglucosamine, both in vitro and in the foregut of its flea vector, as well as y3730, encoding a functional DGC (13,148). While c-di-GMP is an important factor in driving cell-surface and cell-cell interactions, Starkey et al (145) demonstrated that elevated c-di-GMP levels alone are not sufficient to alter the expression of all of the genes affected following wspF inactivation. Using a ⌬wspF single mutant and a nonaggregative ⌬wspF ⌬pel ⌬psl triple mutant, they demonstrated that the regulation of multiple genes is actually dependent on the aggregative phenotype rather than c-di-GMP overproduction.…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…We first investigated several PAO1-derived mutant strains, such as Psl-or Pel-negative strains, Psl-inducible strain WFPA801 (PAO1, P BADpsl), mucoid strain PDO300 (alginate overproducer), and a rugose small-colony variant (RSCV) MJK8 that displays increased production of the Pel and Psl [38]. PslG significantly inhibited the biofilm formation of all PAO1-derived strains, which included Psl-negative strains and MJK8-derived ∆psl∆pel strain ( Figure 4A).…”
Section: Pslg Inhibited Biofilm Formation and Disrupted Existing Biofmentioning
confidence: 99%